(untitled) (Damascus University Journal for engineering sciences, 2021)
This research studies the forced vibration which is generated during the internal turning cylinders by using chip-Breaking flutes. These flutes are spiral with big pitch formed on the surface of the working-piece for breaking the chip to small pieces that can be easily moved away from the cutting place. These flutes periodically cause a change in the section of the cutting layer which cause a creation of the forced vibration motion, it has been found the differential equations that represent the motion of the system and studying the characteristics of "amplitude-frequency" and the effects of cutting depth, feeding, cutting speed and the depth of the flute on them. As a result it has been found a stability field for the studied motion of the technological system in which the amplitude of the generated vibration is nearly constant and it has a small effect on the accuracy of the working pieces